Effect of sulfite on the sensorial quality of minimally processed jackfruit (Artocarpus heterophyllus Lam) - Gepes, Reah Paguntalan
Vegetable vendors in Iloilo City Terminal Market (ICTM) practice the use of sodium metabisulfite on minimally processed jackfruit in order to minimize browning and intensify consumer acceptability.